2015
DOI: 10.1080/14703297.2015.1015595
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of blended learning in interior design education

Abstract: This study explores how blended learning can contribute to interior design students' learning outcomes, their engagement with non-studio courses and affect their learning achievements. Within the framework of the study, a blended learning experience was carried out in 'IAED 342 Building Performance' module at Bilkent University, Turkey. A total of 120 interior architecture students were surveyed about their experiences on five fields of instruction: (1) course design, learning material and electronic course en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…Students are experiencing pleasure, fun, and excitement while learning ballet skills (Ryan and Deci, 2000). BL approach created a positive and productive learning environment as the FTF approach while contributing to the teaching process Afacan, (2016). Computer network technology has brought tremendous changes to people's life (Le, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Students are experiencing pleasure, fun, and excitement while learning ballet skills (Ryan and Deci, 2000). BL approach created a positive and productive learning environment as the FTF approach while contributing to the teaching process Afacan, (2016). Computer network technology has brought tremendous changes to people's life (Le, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also suggest that the key to the successful implementation of online collaboration in design depends on high student participation rates and quick instructor feedback (Bender & Vredevoogd, 2006). Investigators Afacan (2016) and also Power and Kannara (2016) found that ease of navigation and well-designed modules are critical to the success of student-centric virtual studios. Investigators also found that training on internet tools positively impacts both student and teacher engagement in the course material; the smooth operation of technology platforms and tools can make or break a blended or online design class (Power & Kannara, 2016).…”
Section: What Can Be Learned From Existing Research Specific To Onlinmentioning
confidence: 99%
“…Hybrid learning increases the effectiveness of interaction and expands the network in the learning process, even all students and collaborators can network with the business world as source mobilization [14]. In the Indonesian context, quipper as a hybrid learning media has been used in research and provides more value to instructional teachers [15,16].…”
Section: Introductionmentioning
confidence: 99%